Did States Use Implementation Discretion to Reduce the Stringency of NCLB? Evidence From a Database of State Regulations. (January 2018) - Wong, Vivian C.; Wing, Coady; Martin, David; Krishnamachari, Anandita
When No Child Left Behind (NCLB) became law in 2002, it was viewed as an effort to create uniform standards for students and schools across the country. More than a decade later, we know surprisingly little about how states actually implemented NCLB and the extent to which state implementation decisions managed to undo the centralizing objectives of the law. This paper introduces a state-level measure of NCLB stringency that helps shed light on these issues. The measure is available for 49 states and the District of Columbia and covers most years under NCLB (2003–2011). Importantly, the measure does not depend on population characteristics of the state. It varies only because of state-level decisions about rule exemptions, standards, and proficiency trajectories. Overall, we find that while NCLB was successful in encouraging states to adopt higher and more consistent performance standards for schools, it also provided much more flexibility and customization in state-level accountability policies than is generally realized.